Educational view of the Islamic leadership: are the Islamic leaders performing their responsibilities? - Abd Rashid, Adnan; Mamat , Arifin (Centre for Promoting Ideas, USA, 2013)
ISLAM is a religion that puts emphasis on the overall human life. It covers all aspects of the physical body, the soul or the spirit, the emotion and the intellect with the sole purpose of producing individuals who are able wholeheartedly enslave themselves to the Allah almighty in all sectors of their lives. This paper thus discusses on the responsibilities of a leader from the educational perspective. Inadvertently, the drive or thrust of an Islamic State does not encompass the administrative matters and the physical development only. However, it encompasses the efforts to develop human beings or individuals who are pure in mind, pure of heart and pure in deeds where they can function as a member of society who is civilized and has a high self-esteem. An individual’s awareness towards one’s responsibilities and a high self-esteem can bring for a peaceful and harmonious nation in spite of it being multi-racial and multi-religion. An Islamic society is form base on an irrevocable piety to the Almighty Creator. Thus, the establishment of the Islamic society base on the voice of development combines with material values and humanity. Because of this, the role of leaders of Islamic society should be proactive in plotting the path of a nation’s educational system based on piety and faith. This is because education is the basic element in the development of mankind as well as the nation towards an excellent and outstanding society. The characteristic of Islamic Leadership that emphasizes a transparent and permeable culture makes it a high priority with the integrity of individuals as the core that can push forward an Islamic society towards an era that is excellent and glorious. Aside from that, the scenario of the role and responsibilities of leaders can make an individual realize and aware of the importance of piety, faith and self-esteem that create good geography and climate. It can also guide the economic, social and political aspects as well to nurture and keep the universal tradition and civilization.